Back Cover: A Plausible Simultaneous Synthesis of Amino Acids and Simple Peptides on the Primordial Earth (Angew. Chem. Int. Ed. 31/2014). Issue 31 (27th June 2014) - Parker, Eric T.; Zhou, Manshui; Burton, Aaron S.; Glavin, Daniel P.; Dworkin, Jason P.; Krishnamurthy, Ramanarayanan; Fernández, Facundo M.; Bada, Jeffrey L.
<x xml:space="preserve">Abstract</x> Stanley Miller′s cyanamide experiment went unreported for over 50 years, but was recently explored to study cyanamide‐mediated biomolecule polymerization under early Earth conditions. In their Communication on page 8132 ff., F. M. Fernández, J. L. Bada et al. show that the dimerization of cyanamide in the presence of amino acids and intermediates in the Strecker synthesis of amino acids yields significant levels of dipeptides, which provides evidence that cyanamide enhances polymerization under simulated prebiotic environments. (Background image provided by Ron Miller.)<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>